Comparison of various sol-gel derived metal oxide layers for inverted organic solar cells - Oh, Hyunchul; Krantz, Johannes; Litzov, Ivan; Stubhan, Tobias; Pinna, Luigi; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2011)
Inverted bulk-heterojunction solar cells have recently captured high interest due to their environmental stability as well as compatibility to mass production. This has been enabled by the development of solution processable n-type semiconductors, mainly TiO and ZnO. However, the device performance is strongly correlated to the electronic properties of the interfacial materials, and here specifically to their work function, surface states as well as conductivity and mobility. It is noteworthy to say that these properties are massively determined by the crystallinity and stoichiometry of the metal oxides. In this study, we investigated aluminum-doped zinc oxide (AZO) as charge selective extraction layer for inverted BHJ solar cells. Thin AZO films were characterized with respect to their structural, optical and electrical properties. The performance of organic solar cells with an AZO electron extraction layer (EEL) is compared to the performance of intrinsic ZnO or TiO EELs. We determined the transmittance, absorbance, conductivity and optical band gap of all these different metal oxides. Furthermore, we also built the correlations between doping level of AZO and device performance, and between annealing temperature of AZO and device performance. © 2011 Elsevier B.V.
Keywords: Al doped ZnO (AZO); Charge selective extraction layer; Inverted Organic Solar cells; Sol-Gel synthesis; TiOx; ZnO

Inverted organic solar cells using a solution processed aluminum-doped zinc oxide buffer layer - Stubhan, Tobias; Oh, Hyunchul; Pinna, Luigi; Krantz, Johannes; Litzov, Ivan; Brabec, Christoph (Organic Electronics, 2011)
In this article, we demonstrate a route to solve one of the big challenges in the large scale printing process of organic solar cells, which is the reliable deposition of very thin layers. Especially materials for electron (EIL) and hole injection layers (HIL) (except poly(3,4-ethylene dioxythiophene): (polystyrene sulfonic acid) (PEDOT:PSS)) have a low conductivity and therefore require thin films with only a few tens of nanometers thickness to keep the serial resistance under control. To overcome this limitation, we investigated inverted polymer solar cells with an active layer comprising a blend of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C-butyric acid methyl ester (PCBM) with solution processed aluminum-doped zinc oxide (AZO) EIL. Devices with AZO and intrinsic zinc oxide (i-ZnO) EIL show comparable efficiency at low layer thicknesses of around 30 nm. The conductivity of the doped zinc oxide is found to be three orders of magnitude higher than for the i-ZnO reference. Therefore the buffer layer thickness can be enhanced significantly to more than 100 nm without hampering the solar cell performance, while devices with 100 nm i-ZnO films already suffer from increased series resistance and reduced efficiency. © 2011 Elsevier B.V. All rights reserved.
Keywords: Al doped ZnO; Electron injection layer; Inverted structure; Polymer solar cell; Solution processing; Zinc oxide nanoparticles

Rare-earth ion doped up-conversion materials for photovoltaic applications - Wang, Hao; Batentschuk, Miroslaw; Osvet, Andres; Pinna, Luigi; Brabec, Christoph (Advanced Materials, 2011)
With the aim of utilizing the infrared region of solar radiation to improve solar cell performance, significant progress, including theoretical analysis and experimental achievement, has been made in the field of up-conversion for photovoltaic applications. This Research News article reviews recent progress in the development of rear-earth (RE) ion doped up-conversion materials for solar cell applications. In addition, new trends for RE-ion-doped phosphors are briefly discussed, among them trivalent RE-ion-doped up-conversion materials for organic solar cell applications. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: nonlinear optical materials; phosphors; photovoltaic devices; rare earth ions